Pemikiran Pendidikan Islam Menurut K.H. Hasyim Asy’ari - Dhevin M.Q Agus Puspita W (STAIFAS-Press, 2019)
KH Hasyim Asy'ari is a scholar who was born from an elite family of kiai in the Jombang area, he had studied at various boarding schools in Java before continuing his education to the Hijaz land. Then he returned to Indonesia and established the Tebuireng Jombang boarding school which is famous for its hadith science. The depth of knowledge, and his thinking in education is very brilliant, so he got the title